Keypoints-based heterogeneous graph convolutional networks for construction - Wang, Shuozhi; Yang, Lichao; Zhang, Zichao; Zhao, Yifan (Elsevier, 2023)
Artificial intelligence algorithms employed for classifying excavator-related activities predominantly rely on sensors embedded within individual machinery or computer vision (CV) techniques encompassing a large scene. The existing CV-based methods are often difficult to tackle an image including multiple excavators and other cooperating machinery. This study presents a novel framework tailored to the classification of excavator activities, accounting for both the excavator itself and the dumpers collaborating with the excavator during operations. Distinct from most existing related studies, this method centres on the transformed heterogeneous graph data constructed using the keypoints of all cooperating machinery extracted from an image. The resulting model leverages the relationships between the mechanical components of an excavator in varying activation states and the associations between the excavator and the collaborating machinery. The framework commences with a novel definition of keypoints representing different machinery relevant to the targetted activities. A customised Machinery Keypoint R-CNN method is then developed to extract these keypoints, forming the basis of graph notes. By considering the type, attribute and edge of nodes, a Heterogeneous Graph Convolutional Network is finally utilised for activity recognition. The results suggest that the proposed framework can effectively predict earthwork activities (with an accuracy of up to 97.5%) when the image encompasses multiple excavators and cooperating machinery. This solution holds promising potential for the automated measurement and management of earthwork productivity within the construction industry. Code and data are available at: https://github.com/gillesflash/Keypoints-Based-Heterogeneous-Graph-Convolutional-Networks.git.
Keywords: Activity classification; Computer vision; Graph convolutional networks; Keypoint extraction